Combined Toxicity of Methylparaben and Propylparaben in Artemia salina and Allium cepa Applying Experimental Design - Nolasco, Estela Moraes; da Silva, João Vitor dos Santos; de Paula, João Vitor Vieira; da Silva, Fábio Luciano Caldas; Leitão, Maicon Matos; Araújo, Alessandra Silveira Antunes; Massulo, Andreia de Oliveira; Machulek Jr., Amilcar; de Melo da Silva, Lucas (Orbital: The Electronic Journal of Chemistry, 2023)
Parabens are used as preservatives in sanitizers and cosmetic products causing environmental concern, because presented potential as endocrine disrupters. Among these compounds, the most used are methylparaben and propylparaben. Thus, a study was proposed to evaluate the interaction between different concentrations (mmol L-1) of the variables methylparaben [MP] and propylparaben [PP], against the acute toxicity of the microcrustacean Artemia salina (A. salina) and Allium cepa (A. cepa) applying the 22 factorial design with an added center point. Responses were used: percent A. salina mortality (% mortality), A. cepa root growth inhibition (% root inhibition) and mitotic index (%MI). For A. salina, after 72 hours of exposure with the combination of concentration ([MP] and [PP] = 0.8 mmol L−1) caused an 80% mortality. While, A. cepa a high cytotoxicity was observed with the mixture of Parabens, exhibiting 72.3% root growth inhibition at [MP] = 1.2 mmol L-1 with [PP] = 1.2 mmol L-1. In contrast, for response %MI at [MP] = 0.3 mmol L-1 with [PP] = 0.3 mmol L-1, 2.5 %MI with 36% inhibition. In this context, parabens demonstrated high toxicity for A. salina and cytotoxicity for A. cepa, based on the interaction with the effect of the concentrations.